ADMINISTRASI TATA LAKSANA SEKOLAH DALAM MENINGKATKAN EFEKTIVITAS PENGELOLAAN PENDIDIKAN - Meti Fatimah; Fityatul Muharromah (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
School administrative governance plays a fundamental role in ensuring the sustainability and effectiveness of educational management. Well-organized administrative procedures function not merely as technical routines, but also as a strategic support system for decision-making, accountability, and quality educational services. This article aims to examine the role of school administrative governance in enhancing the effectiveness of educational management and to identify adaptive administrative practices in response to contemporary challenges. This study employs a qualitative approach through literature review and descriptive analysis of school administrative practices. The findings indicate that systematic, transparent, and collaborative administrative governance significantly supports overall school performance, enhances the professionalism of educational staff, and fosters an orderly and conducive school climate. These results emphasize that strengthening school administrative governance should be positioned as a strategic component in improving educational quality.